Allogeneic transplantation is not superior to chemotherapy in most patients over 40 years of age with Philadelphia‐negative acute lymphoblastic leukemia in first remission. Issue 8 (3rd June 2016) - Wolach, Ofir; Stevenson, Kristen E.; Wadleigh, Martha; DeAngelo, Daniel J.; Steensma, David P.; Ballen, Karen K.; Soiffer, Robert J.; Antin, Joseph H.; Neuberg, Donna S.; Ho, Vincent T.; Stone, Richard M.
Abstract : Survival of patients ≥40 years of age with Philadelphia‐negative acute lymphoblastic leukemia (ALL) remains poor with current therapeutic approaches. It is unknown whether allogeneic hematopoietic stem‐cell transplantation (HSCT) in first remission confers a survival benefit compared to a chemotherapy‐only approach. We retrospectively compared the outcome of patients >40 years treated with HSCT or chemotherapy alone in first remission ( n  = 40 in each cohort). Three‐year overall survival (OS) and disease‐free survival (DFS) were not significantly different between the chemotherapy‐only and HSCT groups (OS, 46% [31–68] vs. 40% [27–59], P  = 0.35; DFS, 31% [18–52] vs. 40% [27–59], P  = 0.98). The 3‐year cumulative incidence of relapse (CIR) and non‐relapse mortality (NRM) were 61% [41–76] and 9% [2–21] for the chemotherapy‐only group and 28% [15–43] and 32% [17–47] for the transplant group (CIR, P  = 0.011; NRM, P  = 0.014). Allogeneic transplantation for patients ≥40 years with Ph‐negative ALL in first remission is associated with a lower CIR, but this benefit is offset by considerable NRM as compared with chemotherapy‐only approach. HSCT may be beneficial in patients with high‐risk disease features. Am. J. Hematol. 91:793–799, 2016. © 2016 Wiley Periodicals, Inc.